The Biological Properties of Lactoferrin - Grzegorz Trybek; Marcin Metlerski; Kamila Szumilas; Magda Aniko-Włodarczyk; Olga Preuss; Katarzyna Grocholewicz; Barbara Wiszniewska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Lactoferrin (LF) is an iron-binding glycoprotein from the transferrin family, which has been identified in most biological fluids as secretions from exocrine glands and the content of specific granules of neutrophils. It has been reported to have numerous functions. Due to antimicrobial and anti-inflammatory activity, the lactoferrin plays significant role in host defense against infection and extreme inflammation. Recent studies have also demonstrated that LF can protect against cancer in experimental animals and has anticarcinogenic activity in many human tumors. At the cellular level, LF modulates the proliferation, differentiation, maturation, activation, migration and function of immune cells. This review presents the multifunctional roles and specific beneficial properties of lactoferrin.